History Behind Diversity: Muslim and Hindu Relations in East Cakranegara Village, West Lombok - Anggriani, Ni Ketut; Darmawan, Wawan (HISTORIA: Jurnal Program Studi Pendidikan Sejarah, 2025)
This study aims to examine the history of diversity in Lombok, especially in East Cakranegara Village, then explore more deeply related to the relations that exist between Muslim and Hindu communities in the village. Cakranegara is one of the areas in West Lombok that has a diverse population. This is inseparable from the history of the Karangasem kingdom that once ruled Lombok. Religious pluralism reflected in the activities of the community in East Cakranegara Village shows that harmony is established not without reason but there is an underlying history, so it is necessary to conduct further research on how the dynamics of society are established in the midst of differences in beliefs between religious communities. It will certainly affect the knowledge of the community that is able to foster tolerance, tolerance, and empathy that makes people live in harmony amid differences.  This research uses historical research methods that include heuristics/source collection, source verification/critique, interpretation, and historiography. The results of the discussion of this paper explain that the interaction between Muslims and Hindus is well established, as evidenced by the activities they do together during the religious ceremonies of each religion.